Synthesis and Characterization of Cellulose Acetate Membranes from Kepok Banana Stem (Musa acuminata x balbisiana) For Microfiltration Process - Fitria Nur Anissa; Selastia Yuliati; Adi Syakdani (Program studi Teknik Kimia UNS, 2023)
Abstract. Membrane is a separation technology between permeate and feed. The challenge in applying this technology is related to the ingredients that can cause fouling. Cellulose acetate membrane is a porous membrane as a solution to overcome fouling problems.The selectivity level of cellulose acetate membranes in the microfiltration process for water and wastewater treatment is very high. Utilization of kepok banana frond waste as an alternative material for making cellulose acetate membranes that are biodegradable, can be decomposed quickly by microorganisms with a limited shelf life. The aim of this research is to apply cellulose acetate membranes from kepok banana fronds for the microfiltration process in water and wastewater treatment with varying concentrations of acetone using the phase inversion method. The cellulose content contained in the kepok banana fronds is 54.3%. The composition for making the membrane is 2 gr cellulose acetate; PVA 20 ml; and PEG 1.7 ml with various concentrations of acetone 15, 20 and 25 ml. The results of the SEM test of the membrane with a concentration of 25 ml of acetone solvent had the best characteristics with a pore size of 0.0932 μm; thickness of 1.778 mm and swelling index of 9.87%. The highest average flux value was owned by the membrane with a concentration of 20 ml, namely 71.3444 l/m².hour The lowest flux value was owned by the membrane with a concentration of 25 ml, namely 55.5549 l/m².hour.Keywords:Membrane, Microfiltration, Cellulose Acetate, Banana Frond, Acetone